2017
DOI: 10.1002/ijc.30695
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of cervical cancer screening methods in low- and middle-income countries: A systematic review

Abstract: The incidence of cervical cancer in low- and middle-income countries (LMICs) is five times higher than that observed in high-income countries (HICs). This discrepancy is largely attributed to the implementation of cytology-based screening programmes in HICs. However, due to reduced health system infrastructure requirements, HPV testing (self- and provider-collected) and visual inspection with acetic acid (VIA) have been proposed as alternatives that may be better suited to LMICs. Knowing the relative value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(154 citation statements)
references
References 32 publications
2
138
0
8
Order By: Relevance
“…34 Future effective screening is more appropriately based on HPV testing of self-collected samples, followed by diagnosis and treatment of detected precancer in women with established chronic HPV infection. 35 Prevention programs for HIV have focused on avoiding infection, and on prevention of clinical manifestations of AIDS through treatment of infected individuals with antiretroviral therapies (ART). This has been successful in reducing population prevalence of HIV and deaths from HIV-AIDS in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…34 Future effective screening is more appropriately based on HPV testing of self-collected samples, followed by diagnosis and treatment of detected precancer in women with established chronic HPV infection. 35 Prevention programs for HIV have focused on avoiding infection, and on prevention of clinical manifestations of AIDS through treatment of infected individuals with antiretroviral therapies (ART). This has been successful in reducing population prevalence of HIV and deaths from HIV-AIDS in Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not compare the cost-effectiveness of cytology and hrHPV testing in this study, several studies in China and other low- and middle-income countries have already confirmed that HPV testing is more cost-effective than cytology for cervical cancer screening [33, 34]. In addition, the careHPV test (Qiagen), a simple and self-obtained HPV test that can provide results within 3 h, has already been evaluated in rural China, and its accuracy is similar to that of the HC2 test, indicating that the careHPV test is a promising primary screening method in low-resource settings [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer rates are high in LMICs despite cervical cancer being preventable and prevention methods, such as human papillomavirus (HPV) vaccination and cervical cancer screening, being highly cost effective. 11,12 In 2012, HPV vaccination would have cost $0.23 per capita in low-income countries and $0.40 per capita in upper-middle-income countries, and screening and treatment of precancerous lesions and early cervical cancer would have cost $0.26 per capita in low-income countries and $0.87 per capita in upper-middle income countries. 13 GAVI, the Vaccine Alliance provides support for HPV vaccinations in LMICs and has negotiated vaccine delivery pricing since 2013-lowering it from over $100 per dose to $4.50-4.60 per dose-although cost is still a barrier to implementing national HPV vaccination programs in LMICs.…”
Section: Cervical Cancer Inequitymentioning
confidence: 99%
“…Among screening methods used in LMICs, VIA and HPV testing are deemed more effective and less costly than cytology. 11 However, that cytology is still regarded as the gold standard for cervical cancer screening in HICs suggests the importance of questioning the fairness of administering suboptimal screening to women in LMICs due to resource scarcity. We advocate using the most effective screening methods that are available, feasible, and culturally acceptable in LMICs.…”
Section: Preventionmentioning
confidence: 99%